Criminal Law Enforcement for Perpetrators of Hate Speech on Social Media - Emiel Salim Siregar; Dicky Abdillah; Mirza Syapiq; Apriola Dwi Indraswary; M. Irvansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Social media is part of the needs of the Indonesian people that cannot be separated again in line with the times. All public behavior, including social media, is regulated by law. Many people abuse social media to use hate speech in cyberspace, without realizing that their actions are illegal. The purpose of this study is to determine criminal liability for hate speech actors on social media. This study uses empirical legal research methods in which the law looks at social phenomena in the community to find solutions to existing legal problems then linked to laws and regulations. The results of the study found that many Indonesian people use social media to use hate speech. It happens because they do not understand the existing law. However, mistakes and omissions are individuals’ responsibility as legal subjects. Suggestions that can be submitted are reforming the ITE law, socialization to the public by law enforcement related to education and law enforcement and the community itself should be smarter in using social media.